2020
DOI: 10.3346/jkms.2020.35.e120
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin as a Useful Non-Invasive Screening Marker for Eosinophilic Gastrointestinal Disorder in Korean Children

Abstract: Background: Eosinophilic gastrointestinal disorder (EoGID) is an emerging disease condition in Korean children, but its diagnosis requires invasive endoscopic biopsies. Fecal calprotectin (FCal) is a noninvasive biomarker for intestinal inflammation to differentiate organic gastrointestinal diseases from functional abdominal pain disorder. This study aimed to evaluate the diagnostic accuracy of FCal and to determine the optimal cutoff to differentiate EoGID from functional abdominal pain disorder. Methods: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…fCal increased after infection, but levels remained within the normal limits and did not correlate with neutrophils circulating in the peripheral blood. However, interestingly, calprotectin has been shown to be expressed by eosinophils in mice( 30 ) and is elevated in eosinophilic gastrointestinal disorders( 31 ) therefore the changes in fCal levels observed in the current study could be of eosinophilic origin. We also measured HNL in feces as a specific marker for neutrophil inflammation( 32 ) and detected no increase in this marker, supporting the idea of a local, specific eosinophilic-driven response to hookworm infection.…”
Section: Discussionmentioning
confidence: 70%
“…fCal increased after infection, but levels remained within the normal limits and did not correlate with neutrophils circulating in the peripheral blood. However, interestingly, calprotectin has been shown to be expressed by eosinophils in mice( 30 ) and is elevated in eosinophilic gastrointestinal disorders( 31 ) therefore the changes in fCal levels observed in the current study could be of eosinophilic origin. We also measured HNL in feces as a specific marker for neutrophil inflammation( 32 ) and detected no increase in this marker, supporting the idea of a local, specific eosinophilic-driven response to hookworm infection.…”
Section: Discussionmentioning
confidence: 70%
“…Unlike the FC concentration, which showed a significant difference between the age groups, no sig-Most of the reported articles had been about IBD patients, infant diarrhea, and meta-analysis results of the IBD patient group[17] as well as review articles[18][19][20]. Studies on FC are Thus, we conducted this study on healthy male and female adults residing in Jeju, between the age of 30 and 90, to understand the normal range of FC concentration.Another notable finding in the present study's results is that FC showed a statistically significant difference between males and females.…”
mentioning
confidence: 99%
“…FC is a neutrophil-derived substance released during cell disruption and death in the gastrointestinal tract, and is widely used as a screening test for inflammatory bowel disease (IBD), colorectal cancer, celiac disease, and necrotizing enterocolitis of newborns. 14 15 It is also popularly used for monitoring disease activity in patients with IBD. 6 7 16 Several previous studies have proposed the potential role of FC in identifying colorectal polyps.…”
Section: Discussionmentioning
confidence: 99%